Development of Digital Video-Based Dance Media to Improve Elementary School Students' Dance Skills - Neng Awistiani; Astri Sutisnawati; Din Azwar Uswatun (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to develop a Digital Video-Based Dance (V-Tari) media, determine the feasibility of the media, and test its effectiveness in improving elementary school students' dancing skills. The study used the Research and Development (R&D) method with a 4D development model that includes the Define , Design , Develop , and Disseminate stages. The research subjects consisted of 20 fifth-grade students of SDN Sinarmulya. The results showed that the V-Tari media obtained an average validation score of 3.80 with a very feasible category. Student responses to the use of the media reached 88.44% with a very good category. The results of the normality test showed that the data were normally distributed (Sig. = 0.226 > 0.05), while the paired sample t-test showed a significant difference between the pretest and posttest scores (Sig. = 0.000 < 0.05). The average value of dancing skills increased from 61.75 to 88.75 after the use of the media. The effect size value of 3.441 is categorized as large and the N-Gain value of 0.706 is categorized as high. Thus, the Digital Video-Based Dance (V-Tari) media is declared feasible and effective in improving the dance skills of elementary school students.